History and philosophy of computing : third International Conference, HaPoC 2015, Pisa, Italy, October 8-11, 2015, Revised selected papers /: third International Conference, HaPoC 2015, Pisa, Italy, October 8-11, 2015, Revised selected papers. (2016) - Unknown
No abstract available